Systematic literature review (SLR) on the factors affecting distribution of natural lighting inside classrooms / Wan Nur Hanani Wan Abdullah, Asniza Hamimi Abdul Tharimand Asmat Ismail - Wan Abdullah, Wan Nur Hanani; Hamimi, Asniza; Ismail, Asmat (2019)
The natural lighting concept is to bring daylight into the area of buildings. The advantage of using natural lighting is that artificial lighting is reduced and solar energy is used directly. Adapting natural light design to a building is challenging and educational buildings are building typology that requires efficient lighting conditions. There was a huge cost burden when most educational buildings use high lighting energy consumption. Problems caused by insufficient natural lighting, result in high lighting energy consumption rates due to the use of alternative artificial lighting. It is the designer's responsibility to consider the design of daylight design building to be adapted to every construction process and design phase. Therefore, this paper aims to review a few factors that affect the distribution of natural lighting inside classrooms by using a systematic literature review (SLR) method. This paper also reviews the best practice of building natural lighting design features. A systematic review of Scopus and GoogleScholar databases identified 23 related studies. Further review of these articles resulted in six main factors that affect distribution of natural lighting inside the classroom.